WordHoard. - ULLYOT, MICHAEL (Renaissance & Reformation / Renaissance et Réforme, 2018)
The article discusses at software application WordHoard, a java application created for the computational analysis of Classical, Medieval, and Early Modern texts, created by Martin Mueller and Bill Parod, available at wordhoard.northwestern.edu/userman/index.html.